The Effect of Various Surface Treatment on the New Digitally Manufactured Materials Versus the Conventional Materials – In Vitro Study (Asian Journal of Pharmaceutics (AJP), 2024)
Background: Clinical benefits of resilient denture liners have been recognized in prosthodontic practice for manyyears. The elastic behavior of the soft lining materials is designed to distribute functional and non-functionalstress on denture-supporting tissues. Materials and Methods: A total of 30 dumbbell-shaped test specimens wereprepared from two different heat cure denture base materials. They are divided into two groups. Group (A) wasprepared from heat cure poly-methylmethacrylate resin (PMMA) and Group (B) was prepared from computeraideddesign and computer-aided manufacturing (CAD/CAM) acrylic resin denture base material. A temporarysoft-liner type was used. The denture base specimens of (Group A and Group B) were subdivided equally intothree subgroups. 3 mm was marked and sectioned on the specimens with fissure burs and removed to createa uniform space for the application of soft liner. The interface surface of each specimen and the denture baseresin surface were conditioned by three surface treatment modalities: 1 – specimens were polished using siliconecarbide papers of grit size, 2 – using air abrasion by 50 μm aluminum oxide particle, 3 – by application of 3 MScotchbond dental adhesive. Tensile bond strength (TBS) was tested for the specimens of each subgroup afterthermocycling. Results: The mean of TBS of subgroup (A3) and subgroup (B3) specimens treated with 3MScotch bond was significantly higher than the other subgroups. Conclusion: The surface treatment of PMMAand CAD/CAM denture base specimens with primer followed using an adhesive bond of 3M Scotch bond had aneffective and superior TBS.